Evaluation of Laxatife ffect and Fermentabilitiy of Gel Forming Component ofGreen cingcau Leaves(Premna oblongifolia Merr.) - Samsu Udayana Nurdin (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2007)
The major effects of dietary fibre occur in the colon. Each type of dietary fibre interacts with the microflora, and the colonic mucosa and muscle to produce several possible effects. The action of an individual fibre source depends to a large extent on its fermentability. The least fermentable dietary fibres are in general having the greatest effects on stool output. Previous research showed that Gel Forming Component (GFC) of green cingcau leaves (Premna oblongifolia Merr.) had high fermentability in vitro. Therefore, in this research, we evaluated its effecton stool output and viable cells number of lactic acid bacteria in the diegesta of rats fed with diet containing GFC. Fifteen of 3 months-old Sparague-Dawle (c)and (3) Rats fed with diet containing iulin (l). The results showed that stool output of G was higher than l, but lower than C (6.30, 4.61, 7.21%, (respectively). feces consistency of G was softer than l, but harder than C. Number of viable cells of latic acid bacteria in the diegesta of G, I, and C were 12.85, 11.97 and 11.14 log of viable cells numbe/g digesta, respectively. These data suggest that GFC of green cingcau leaves had moderate laxative effect and fermentability. Key words: cingcau, fermentability, laxative, dietary fibre.